The serum acylcarnitines profile in epileptic children treated with valproic acid and the protective roles of peroxisome proliferator-activated receptor a activation in valproic acid-induced liver injury - Ma, Yiyi; Wang, Minglu; Guo, Shuaishuai; Li, Tong; Liu, Xiaodong; Zhao, Limei (Frontiers in Pharmacology, 2022)
Valproic acid (VPA) is widely used as a major drug in the treatment of epilepsy. Despite the undisputed pharmacological importance and effectiveness of VPA, its potential hepatotoxicity is still a major concern. Being a simple fatty acid, the hepatotoxicity induced by VPA has long been considered to be due primarily to its interference with fatty acid β-oxidation (β-FAO). The aim of this study was to investigate the biomarkers for VPA-induced abnormal liver function in epileptic children and to determine potential mechanisms of its liver injury. Targeted metabolomics analysis of acylcarnitines (ACs) was performed in children’s serum. Metabolomic analysis revealed that VPA -induced abnormal liver function resulted in the accumulation of serum long-chain acylcarnitines (LCACs), and the reduced expression of β-FAO relevant genes (Carnitine palmitoyltrans-ferase (CPT)1, CPT2 and Long-chain acyl-CoA dehydrogenase (LCAD)), indicating the disruption of β-FAO. As direct peroxisome proliferator-activated receptor α (PPARα)- regulated genes, CPT1A, CPT2 and LCAD were up-regulated after treatment with PPARα agonist, fenofibrate (Feno), indicating the improvement of β-FAO. Feno significantly ameliorated the accumulation of various lipids in the plasma of VPA-induced hepatotoxic mice by activating PPARα, significantly reduced the plasma ACs concentration, and attenuated VPA-induced hepatic steatosis. Enhanced oxidative stress and induced by VPA exposure were significantly recovered using Feno treatment. In conclusion, this study indicates VPA-induced β-FAO disruption might lead to liver injury, and a significant Feno protection effect against VPA -induced hepatotoxicity through reversing fatty acid metabolism.